A Comparative Study of the Efficacy of Methylprednisolone Administration Route on Postoperative Sequelae Following Impacted Third Molar Extraction - Bijayalaxmi Panigrahi; Santosh Kumar Subudhi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Surgery on the lower-impacted third molar typically includes injury to the heavily vascularizedloose connective tissue due to its anatomical location, leading to inflammatory sequelae during the immediatepost-operative stage, including postoperative pain, oedema and trismus.Aims: This prospective, randomized, comparative clinical study was conducted in 30 patients to assess pain,oedema and trismus in patients undergoing surgical removal of impacted third molars.Method: The study sample involves 30 patients, randomly categorized into 3 groups: group 1 (control;no steroids), group 2 (Intra-Muscular injection in Masseter muscle), group 3 (oral tablets). Patient agedbetween 18 and 30, with a similar anatomical position, and similar surgical difficulty, no allergies, withoutany systemic diseases are included. Syndromic patients, patients with periapical pathologies were excludedfrom the study. A single surgeon was working on all patients using a standard technique. On the 2ndand 7th postoperative day, linear oedema and maximal mouth opening were evaluated for both routes ofmethylprednisolone administration and compared.Results: We observed a higher range of mouth opening found in masseter injection group relative to theoral tablet group on Day 2 & 7, for the steroid treatment groups. On postoperative days 2 and 7, the overallincrease in the tragus-commissure, canthus-gonion and tragus-pogonion lines, for control & oral tabletgroups were identical and higher than the masseter injection group.Conclusion: Comparison to the control group following lower third molar surgery, intramassetric injectionprovided improved outcomes than tablet form in limiting oedema and trismus